Peran Guru Pendamping Khusus Dalam Mendukung Program Inklusi di TKIT Lentera Insan CDEC Depok - Yunitasari, Septiyani Endang; Emelda, Emelda; Nofrianto, Robby; Heryani, Yeni; Eliyanah, Eliyanah; Hafid, Pera Yulia (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2024)
Education inclusion is an approach aimed at ensuring that children with various needs receive equal and supportive education. The inclusion program at TKIT Lentera Insan CDEC Depok provides valuable opportunities for children with special needs to socialize and integrate into the school community. The role of special education teachers is crucial in creating a conducive learning environment. This article discusses the role of special education teachers in supporting the inclusion program at TKIT Lentera Insan CDEC Depok, with a focus on their efforts to ensure the success of children with special needs.